Depth of Anesthesia as a Risk Factor for Perioperative Morbidity - Argyro Petsiti; Vassilios Tassoudis; George Vretzakis; Dimitrios Zacharoulis; Konstantinos Tepetes; Georgia Ganeli; Menelaos Karanikolas (Anesthesiology Research and Practice)
Introduction. The prognostic value of age, physical status, and duration of surgery on perioperative course has been extensively studied. However, the impact of deep hypnotic time (time when Bispectral Index values are less than 40) has not been well evaluated. Methods. We designed an observational study to clarify the relative influence of deep hypnotic time (DHT) on outcome. Eligible participants were mentally stable patients over 18 years old scheduled for elective major abdominal surgery. In total, 248 patients enrolled. Data were analyzed using Fisher’s exact test and multiple logistic regression. Results. Five variables (DHT, hypotension, age, comorbidity, and duration of surgery) showed statistically significant association with complications, when examined independently. However, when all variables were examined together in a multiple logistic regression model, age and comorbidity were no longer associated with outcome. DHT, hypotension, and duration of surgery were significant predictors of “complications,” and “hypotension” was a significant predictor of prolonged hospital stay (P<0.001).  Conclusion. Deep hypnotic time emerged as a new factor associated with outcome, and its impact compared to other factors such as age, surgery duration, hypotension, and comorbidity is redefined. Monitoring and managing depth of anesthesia during surgery are important and should be part of careful operation planning.